American Poetry: The Modernist Ideal
IX, 274 p.
Keywords: Tracing its origins back to Walt Whitman, the Modernist tradition in American poetry is driven by the same concern to engage with the world in revolutionary terms, inspired by the concept of democracy vital to the American dream. But this tradition is not confined to a few writers at the beginning of the century: instead it has been an enduring force, extending from coast to coast and of varying hues: Imagist, Objectivist, Beat. International in flavour but shaped by the language and conditions of America, this poetry continues to speak to us today. This collection of specially commissioned essays brings together leading scholars and critics to define the American Modernist canon, providing a range of perspectives helpful to all those interested in this fascinating poetry.